The Little Data Book on Information and Communication Technology 2008 - World Bank (World Development Indicators, 2008)
Now in its second edition, the Little Data Book on Information and Communication Technology 2008 presents at-a-glance tables for over 140 economies showing the most recent national data on key indicators of information and communications technology (ICT), including access, quality, affordability, efficiency, sustainability, and applications